Toxicity assessment of green synthesized Cu nanoparticles by cell-free extract of Pseudomonas silesiensis as antitumor cancer and antimicrobial - Gehan F. Galal; Basma T. Abd-Elhalim; Khadiga A. Abou-Taleb; Ahmed A. Haroun; Rawia F. Gamal (Annals of Agricultural Sciences, 2021)
Spherical homogeneous 32 nm, protein coated Pseudomonas silesiensis strain A3 CuNPs was investigated for their cytotoxicity effect as well as antimicrobial and antitumor activity. CuNPs cytotoxicity was estimated using human normal lung cell lines (Wi38) against CuNPs with concentrations ranging from 25 to 150 μg/mL using neutral red uptake assay. The cytotoxicity study revealed that the bacterial CuNPs had an impact on Wi38 cell viability at concentrations of 25, 50, 100 and 150 μg/mL CuNPs were 95.8, 91.1, 89.2 and 82.3%, respectively, with a strong correlation coefficient (r = 0.94) and a CuNPs IC50 value of 1057.0 μg/mL. CuNPs exhibit a broad-spectrum antimicrobial activity against various microorganism species, including fungi and Gram positive and negative bacteria using the agar-well diffusion method. The findings revealed that the most sensitive pathogens were Staphylococcus aureus ATCC5638 and Aspergillus flavus ATCC 9643 which tended to have a high inhibition zone diameter (50 and 47 mm, respectively). The minimum inhibitory concentration (MIC) of CuNPs was 50 μg/mL. The minimum lethal concentration (MLC) values were 50 and 75 μg/mL for S. aureus ATCC 5638 and A. flavus ATCC 9643, respectively. MLC/MIC ratio was ≤2, suggesting the CuNPs had a bactericidal or fungicidal effect on both pathogenic strains. Results also indicated that bacterial CuNPs at varying concentrations of 25, 50, 100 and 150 μg/mL were such a good antitumor agent against A549 lung carcinoma cell lines with an IC50 value of 137.5 μg/mL and a cell viability of 89.3, 79.6, 64.9 and 44.1%, respectively. The results also suggested that the biosynthesized-CuNPs were an antimicrobial and anticancer agent that could be used in future in food preservation, biomedicine and pharmaceutical fields.